Tectona grandis L.f. clonal selection for the dry Pacific zone of Costa Rica - Badilla-Valverde, Yorleny (2022)
Teak has the highest value of any commercially planted tree species in the tropics. The tree improvement international cooperative GENFORES, established in Costa Rica, has led breeding programs with this tree species in Latin America. This investigation was undertaken with the objective of selecting the clones which are best adapted to the dry Pacific zone of Costa Rica, as well as for other dry regions in the tropics. Research was carried out in Nicoya, in the province of Guanacaste (in the northern Pacific region of Costa Rica), where 31 genotypes were evaluated for 13 continuous years, in terms of diameter growth, commercial volume, and stem quality. Genetic parameters were obtained using Selegen-REML/BLUP software, as were selection rankings and estimated genetic gain. The highest values for individual heritability and mean clonal heritability for diameter (h2g = 0.12 and h2mc = 0.82), and for commercial volume (h2g = 0.075 and h2mc = 0.74) were obtained for trees that were 8.9 years old. Commercial plantations established with the best 10 clones, with an age of 12.9 years, may attain a commercial volume of 0.88 m3 per tree, corresponding to a genetic gain of 11% with respect to the best available seed source from a seed orchard, while diameter would reach 28 cm at the same age. These results allow a reduction of approximately two years of the age at which teak can be harvested in the dry Pacific zone of the country.